Simbol dan Makna Ritual Yaqowiyu di Jatinom Klaten - Mona Erythrea Nur Islami; Muhammad Ikhsanudin (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2014)
Yaqowiyu is one syncretism practice that still survives to this day in Indonesia. Rituals held every “Sapar” evolved since the days of Islamic Mataram. The purpose of the ritual is to remember the great merit of Ki Ageng Gribig, one of the missionaries of Islam in Jatinom Klaten during the reign of the “Sultan Agung Hanyokrokusumo”. Yaqowiyu ritual uniqueness lies in deployment “apem” in peak ceremony, which is a round cake made of rice flour with coconut pieces in the middle. This research aims to reveal the meaning of Yaqowiyu. Research methods used are observation, life history interviews and historical methods are to do an analysis of the documents. The results showed that Javanese people still strongly believe in animism. Yaqowiyu is interpreted as a ritual to maintain the safety and peace embodied by the behaviour of “ngalap berkah”. “Apem” cake meant as a tool to realize their request. But on the other hand, Yaqowiyu also is used as a propaganda strategy to spread the religion of Islam. At this point, Yaqowiyu also is interpreted as a tourist commodity that can be sold.